Association Between Positive Childhood Experiences and Childhood Flourishing Among US Children. Issue 4 (20th May 2023) - Crouch, Elizabeth; Radcliff, Elizabeth; Brown, Monique J.; Hung, Peiyin
ABSTRACT: Objective: There has been limited research examining the fostering of positive childhood experiences (PCEs) that could promote flourishing among children. The purpose of this study is to examine the relationship between 7 selected PCEs and the outcome of flourishing, among a nationally based population-level survey sample of children aged 6 to 17 years. Methods: Data were drawn from the 2018 to 2019 National Survey of Children's Health, with children aged 6 years and older included (n = 40, 561). Children were designated as flourishing if they had responses of always or usually to all 3 flourishing items measured by the National Survey of Children's Health, which were (1) showing an interest and curiosity in learning new things, (2) working to finish the task they started, and (3) staying calm and in control when faced with a challenge. To examine the association between PCEs and flourishing, multivariable logistic regression models were used. Results: Children who experienced each type of PCE had higher odds of flourishing: after-school activities (adjusted odds ratio [aOR], 1.81; 95% confidence interval [CI], 1.58–2.07), community volunteer (aOR, 1.63; 95% CI, 1.47–1.80), guiding mentor (aOR, 1.66; 95% CI, 1.39–2.00), resilient family (aOR, 2.35; 95% CI, 2.08–2.67), safe neighborhood (aOR, 1.43; 95% CI, 1.29–1.60), supportive neighborhood (aOR, 1.57; 95% CI, 1.42–1.74), and connected caregiver (aOR, 3.26; 95% CI, 2.93–3.64). Conclusion: Findings demonstrating a significant association between PCEs and flourishing have implications for population-wide approaches to improving the prevalence of flourishing among children and youth.